Extreme violation of local realism with a hyper-entangled four-photon-eight-qubit Greenberger-Horne-Zelinger state - Lu, Huai-Xin (Nature Publishing Group, 2014)
The highest qubit Ardehali inequality violation with 203 standard deviations is first experimentally demonstrated using the hyper-entangled four-photon-eight-qubit Greenberger-Horne-Zeilinger (GHZ) state. Moreover, we experimentally investigate the robustness of the Ardehali inequality for the four-, six-, and eight-qubit GHZ states in a rotary noisy environment systematically. Our results first validate the Ardehali' theoretical statement of relation between violation of Ardehali inequality and particle number, and proved that Ardehali inequality is more robust against noise in larger number qubit GHZ states, and provided an experimental benchmark for us to estimate the safety of quantum channel in the noisy environment.